Identification of novel variations of oculocutaneous albinism type 2 with Prader–Willi syndrome/Angelman syndrome in two Chinese families - Chen, XiaoFei; Fang, ZiShui; Pang, Ting; Li, DongZhi; Lei, Jie; Jiang, WeiYing; Li, HongYi (Frontiers in Genetics, 2023)
Objective Oculocutaneous albinism (OCA) is an autosomal recessive disorder caused by a variety of genomic variations. Our aim to identify the molecular basis of OCA in two families and lay the foundation for prenatal diagnosis. Methods Four types of OCA-causing mutations in the TYR, P, TYRP1, or SLC45A2 genes were screened. Linkage analysis was performed, because the mutations found in P gene violated the laws of classical Mendelian heredity. Primer-walking sequencing combined with microsatellite and single nucleotide polymorphism analysis were used to ascertain deletion ranges. Bioinformatics methods were used to assess the pathogenicity of the new mutations. Results Proband 1 was diagnosed as OCA2 with PWS due to a novel atypical paternal deletion (chromosome 15: 22330347-26089649) and a pathogenic mutation, c.1327G>A (Val443Ile)，in the P gene of the maternal chromosome. The prenatal diagnosis result for family 1 indicated the fetus was a heterozygous carrier (c.1327G>A in the P gene) with a normal phenotype. Proband 2 was diagnosed as OCA2 with AS due to a typical maternal deletion of chromosome 15q11-q13 and a novel mutation, c.1514T>C (Phe505Ser), in the P gene of the paternal chromosome. This novel mutation c.1514T>C (Phe505Ser) in the P gene was predicted as a pathogenic mutation. Conclusions Our study showed clear genotype-phenotype correlations in patients affected by distinct deletions of the PWS or AS region and missense mutations in the P gene. Our results enriched the mutation spectrum of albinism diseases and provided insights for more accurate diagnosis and genetic counseling.